Branding a New Buddhist Movement: The New Kadampa Tradition’s Self- Identification as “Modern Buddhism” - Emory-Moore, Christopher (Journal of global buddhism, 2020)
This article examines the New Kadampa Tradition’s North American missionary deployment of the epithet “Modern Buddhism” in publicity, text, and teaching. I argue that while “Modern Buddhism” branding supports the NKT’s international growth by promoting its founder’s teachings as universally accessible and not Tibetan, those teachings are more continuous with traditional Geluk doctrine than with David McMahan’s (2008) portrayal of Buddhist modernism. Specifically, I find minimal evidence of detraditionalization, demythologization, and psychologization in the NKT founder’s 2011 book Modern Buddhism and in public meditation instruction derived therefrom at a Canadian NKT center. My findings locate the NKT’s deployment of the “Modern Buddhism” brand within a graduated missionizing strategy that combines promotional modernism and pedagogical traditionalism to attract North American non-Buddhists by offering culturally desired, this-worldly benefits (e.g., stress reduction) followed by less familiar, other-worldly Buddhist goals (e.g., happiness in future lives).